5+3c=-8+-12c

Simple and best practice solution for 5+3c=-8+-12c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+3c=-8+-12c equation:


Simplifying
5 + 3c = -8 + -12c

Solving
5 + 3c = -8 + -12c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '12c' to each side of the equation.
5 + 3c + 12c = -8 + -12c + 12c

Combine like terms: 3c + 12c = 15c
5 + 15c = -8 + -12c + 12c

Combine like terms: -12c + 12c = 0
5 + 15c = -8 + 0
5 + 15c = -8

Add '-5' to each side of the equation.
5 + -5 + 15c = -8 + -5

Combine like terms: 5 + -5 = 0
0 + 15c = -8 + -5
15c = -8 + -5

Combine like terms: -8 + -5 = -13
15c = -13

Divide each side by '15'.
c = -0.8666666667

Simplifying
c = -0.8666666667

See similar equations:

| 8.1+-1.8h=-7.2 | | 200+x(0.15)=348.50 | | 40x+5y=8 | | 91+21x=43x+3 | | 5+3c=-8+-12x | | 2(x-5)+x=4x-1+2x | | 3x-5(x-5)=7+2x+4 | | 6x-3=-11 | | m=10-x | | 8.1+1.8h=-7.2 | | (M-7)(m-3)=0 | | 45-61=4x-2x | | 1.5x+0.5=12 | | 3x-4x=-22 | | bx-ay+2z=-19 | | 72y+4.7=62.3 | | 6x^2-3=x^3-169 | | 4a+5b+c=6 | | -x-3(2)=-11 | | 9r^2+2r-24=0 | | 30x=540 | | 5-4k=12x+7 | | x^2+7x+20=3x+17 | | -9y+3x=-9 | | 95m-2=80a+3 | | 6=10(k+.6) | | 2x+22+122=14x | | m/(-3)=-5-18 | | 6x-5+8x-2x-3=9w-24 | | 0.40x+0.25(140)=0.20(113) | | 5t-2=3t-8+8t | | 3x(5)+3=18 |

Equations solver categories